Outcome of endoscopic fulguration of posterior urethral valves in children - Gupta, Sudip Das; Khatun, AA; Islam, AI; Shameem, IA (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):239-44. The abstract of this article is available on the PubMed website